2009
DOI: 10.1016/j.phrs.2009.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Ki determination and CoMFA analysis of nuclear receptor ligands as competitive inhibitors of OATP1B1-mediated estradiol-17β-glucuronide transport

Abstract: Evidence shows that drug-drug interactions can occur at the level of drug transporters such as the organic anion transporting polypeptides (OATPs), a group of membrane solute carriers that mediate the sodium-independent transport of a wide range of amphipathic organic compounds. The polyspecific OATP1B1 is exclusively expressed at the basolateral membrane of hepatocytes and mediates uptake of amphipathic organic compounds from blood into hepatocytes. Nuclear receptors are ligand-activated transcription factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…The key molecular features identified in this two-dimensional quantitative structure activity relationship approach are consistent with the work of Chang et al (2005) who by use of a three-dimensional pharmacophore approach also identified hydrogen bond accepting and hydrophobicity as key features in OATP1B1 inhibition. These key interactions are further substantiated by Gui et al (2009) who by use of a comparative molecular field analysis approach identified hydrophobicity and basicity of the side chain residues as being critical for OATP1B1 inhibition. Badolo et al (2010) investigated the ability of 179 compounds to inhibit the uptake of estradiol-17␤-glucuronide in human hepatocytes to develop a structure-activity relationship for OATP1B1/1B3.…”
Section: Discussionmentioning
confidence: 86%
“…The key molecular features identified in this two-dimensional quantitative structure activity relationship approach are consistent with the work of Chang et al (2005) who by use of a three-dimensional pharmacophore approach also identified hydrogen bond accepting and hydrophobicity as key features in OATP1B1 inhibition. These key interactions are further substantiated by Gui et al (2009) who by use of a comparative molecular field analysis approach identified hydrophobicity and basicity of the side chain residues as being critical for OATP1B1 inhibition. Badolo et al (2010) investigated the ability of 179 compounds to inhibit the uptake of estradiol-17␤-glucuronide in human hepatocytes to develop a structure-activity relationship for OATP1B1/1B3.…”
Section: Discussionmentioning
confidence: 86%
“…6. This type of analysis has been successfully used previously to determine the type of interaction for a wide range of physiological substrates and fibrates for OATP1B1 (22,23) and the interaction of OATP1B1, OATP1B3, and OATP1C1 with non-steroidal anti-inflammatory drugs (24,25). If an interacting compound is a competitive inhibitor of LY, we can assume that it is being transported by Oatp1d1, in which case the K i value of the interacting compound actually represents its K m value.…”
Section: Resultsmentioning
confidence: 99%
“…To date, studies have primarily focused on single compounds or were not carried out over a sufficiently wide concentration range to achieve the above objectives. In contrast, there are several studies documenting inhibitory properties of many drugs against various hepatic transporters, particularly OATP1B1 (Hirano et al, 2006;Noe et al, 2007;Gui et al, 2009;Sharma et al, 2009). …”
Section: Discussionmentioning
confidence: 99%